KAJIAN KEBERADAAN TEGAKAN TINGGAL DAN KETERHUKAAN LABAN. PADA KEGIATAN PENEBANGAN DAN PENYARADAN DI SUATU PERUSAHAAN HUTAN DI KALIMANTAN TENGAH (The study of residual stand condition and ground exposure caused by felling and yanling ooerations at a forest concession in central Kalimantan) - Sona Suhartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The damages of soil and vegetation caused by felling and yarding operations are unavoidable eventhough the operations are done very carefully.The conclusions of several previous studies related to the problem showed that residual stand damages and ground exposure are influenced by logging operation, because felling and yartling operations are carried out without proper planning.The aim of the study is to find the level of residual stand damage, total trees felled per unit area, and ground exposure caused by felling and yarding operations.The study was carried out in a forest concession of PT Kayu Tribuana Rama in Central Kalimantan in 1991. the gathered data were analysed by simple linier regression analysis.1.The average . of residual stand damage caused by felling and yarding operations is 11.1% for the average total trees felled of 5.9 trees/Ha.2. the effect of total trees felled per unit area on residual stand damage is highly significant. logging operations in Sleeper slope could increase residual stand damage.3. The average of ground exposure caused by logging operation is 19. 7% .for the average total trees felled of 5. 9 trees/ha.4. The effect of total trees felled per unit area cm ground exposure is not significant. logging operations in the company is not planned to comply with TPTI regulations.